Biomass-based water-resistant and oil-resistant packaging paper and preparation method thereof
The modified coating is prepared by pretreatment of calcium chloride solution and biomass raw materials, which solves the problem of insufficient water and oil resistance of paper-based packaging materials, achieves efficient water and oil barrier effects, and improves mechanical properties while ensuring the material biodegradability and environmental protection.
Patent Information
- Application Number
- CN202411601376.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The existing paper-based packaging materials have poor resistance to water and oil surfaces, resulting in limited mechanical properties. The traditional plastic film cover has environmental pollution problems, and biodegradable materials have insufficient water and oil resistance.
The base paper is pretreated with calcium chloride solution, and modified sulfonated nanocellulose and modified lignin nanoparticles are prepared through biomass raw materials, combined with ethyl cellulose and polyvinyl butyral to form a composite water-resistant and oil-resistant coating. Improves the water and oil resistance of paper.
It significantly improves the oil and water resistance of the paper, enhances mechanical properties, and the material is completely biodegradable, harmless to the environment and the human body, and the preparation method is simple and industrially produced.
Smart Images

Figure CN119243516A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of biopolymers, and in particular to a biomass-based water-resistant and oil-resistant packaging paper and a preparation method thereof. Background Art
[0002] Paper-based packaging materials are one of the most promising materials to replace disposable plastic products and solve "white pollution" because of their advantages such as lightness, biodegradability, renewability and mechanical flexibility. So far, the market share of paper-based packaging materials accounts for about 50% of the total packaging industry. However, the surface fibers of paper-based materials are hydrophilic and porous, resulting in poor water resistance and oil resistance. In addition, the adhesion of water and oil on the surface of paper-based materials will seriously affect the mechanical properties of paper, which severely limits the daily use of paper. At present, some specially treated paper-based materials on the market have both water and oil resistance, which well solves the problem of poor barrier properties of paper used for food packaging. Water-resistant and oil-resistant packaging paper is a kind of paper that resists the penetration of grease and water. It is often used to package foods with grease and high water content, such as hamburgers, cakes, traditional Chinese fast food, etc.
[0003] Since paper products themselves are not resistant to water and oil, in order to achieve the purpose of water and oil resistance, most paper products in the early days were covered with plastic film when used. The materials of plastic film, such as low-density polyethylene (LDPE), polyvinyl chloride (PVC), polyethylene terephthalate (PET), etc., cannot degrade by themselves after being discarded. Even if incineration is used, a large amount of waste gas will be generated during the combustion process, which has become a major source of environmental pollution. In addition, the raw materials of these plastic films come from petroleum, which is a non-renewable resource. The large-scale use of plastic film will aggravate the energy crisis. Later, the use of fluorine coating in wrapping paper can achieve good oil resistance, but the application of fluorine coating in food packaging is dangerous. After the fluorine-coated wrapping paper is discarded, it will release fluorine-containing organic matter during the composting process, polluting the soil and affecting people's health.
[0004] As people's awareness of environmental protection and physical health continues to increase, biodegradable materials have gradually become a research hotspot to replace traditional plastic materials due to their environmental protection, non-toxicity and regeneration properties. However, these biodegradable materials cannot truly achieve the dual effects of environmental protection and economy. For example, polylactic acid (PLA) has good biodegradability and mechanical properties, but it is hard and brittle at room temperature, with extremely low elongation at break and impact strength; polyvinyl alcohol (PVA) can be used by bacteria as a carbon source, and has excellent oil resistance and gas barrier properties, but its production process is complex and costly; polybutylene terephthalate (PBAT) has good flexibility, but its heat sealing properties are poor, its texture is soft, and it is easy to deform when stretched, which greatly limits the promotion and application of environmentally friendly biodegradable materials in the packaging field. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and provide a biomass-based water-resistant and oil-resistant packaging paper.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned biomass-based water-resistant and oil-resistant packaging paper.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A method for preparing biomass-based water-resistant and oil-resistant packaging paper comprises the following steps:
[0009] (1) impregnating base paper with a calcium chloride solution having a concentration of 1 to 3% for 4 to 10 minutes, and obtaining pretreated base paper after drying;
[0010] (2) Using biomass raw materials to prepare nanocellulose;
[0011] (3) adding sodium dodecyl sulfate to anhydrous ethanol, stirring and heating at 50-70° C. for reaction for 30-50 min, then adding the nanocellulose obtained in step (2), continuing to stir and heat for reaction, washing, and ultrasonicating to obtain modified sulfonated nanocellulose;
[0012] (4) adding ethyl cellulose to anhydrous ethanol, stirring and heating at 30-50° C. for 20-40 min, then adding the modified sulfonated nanocellulose obtained in step (3) and continuing to stir and heat for 20-40 min to obtain an oil-resistant solution;
[0013] (5) adding alkali lignin to anhydrous ethanol, stirring and heating at 40-60° C. for 40-80 min, then adding water and continuing stirring and heating for 20-40 min, collecting the supernatant, centrifuging at 4000-6000 rpm for 10-30 min, and removing ethanol by rotary evaporation to obtain lignin nanoparticles;
[0014] (6) adding the lignin nanoparticles prepared in step (5), octadecylamine and ferulic acid to anhydrous ethanol, stirring and heating at 50-70° C. for 3-5 h, cooling, filtering and drying to obtain modified lignin nanoparticles;
[0015] (7) adding polyvinyl butyral to anhydrous ethanol, stirring and heating at 40-60° C. for 30-50 min, then adding the modified lignin nanoparticles obtained in step (6), and continuing to stir and heat for 20-40 min to obtain an aqueous solution-resistant nanoparticle;
[0016] (8) stirring and mixing the oil-resistant solution obtained in step (4) and the water-resistant aqueous solution obtained in step (7) for 20 to 40 minutes, and ultrasonicating to obtain a water-resistant and oil-resistant composite solution;
[0017] (9) coating the water-resistant and oil-resistant composite solution obtained in step (8) on the pretreated base paper obtained in step (1), and drying the solution to obtain biomass-based water-resistant and oil-resistant packaging paper.
[0018] The base paper in step (1) is a paper having a rough surface made from raw wood pulp.
[0019] The drying condition of step (1) is drying at 30-50° C. for 5-20 min.
[0020] The biomass raw material in step (2) is a biomass raw material rich in cellulose; preferably coniferous wood pulp or Sargassum fusiformis; more preferably Sargassum fusiformis.
[0021] When the biomass raw material is coniferous wood pulp, the preparation method of nanocellulose is:
[0022] 20 g of bleached softwood pulp was added to a solution prepared by dissolving 0.05 g of TEMPO, 0.5 g of NaBr and 50 mL of NaClO in 500 mL of deionized water. The pH value of the reaction system was adjusted to 10 with 0.1 mol / L HCl and NaOH. The mixture was then homogenized at 180 MPa for 15 times and filtered to obtain softwood pulp nanocellulose.
[0023] When the biomass raw material is Sargassum fusiformis, the preparation method of nanocellulose is:
[0024] The dried Sargassum fusiformis is soaked in water, the soaked Sargassum fusiformis is placed in a 20wt% Na2CO3 solution and mixed evenly for 1 hour, then dried, washed, placed in a 3wt% acetic acid solution to react for 2 hours, then added with a 30wt% H2O2 solution to react for 2 hours, washed, added with deionized water, and then homogenized 20 times at 200MPa, and filtered to obtain Sargassum fusiformis nanocellulose.
[0025] The mass ratio of sodium dodecyl sulfate to nanocellulose in step (3) is 1-2:1-2; preferably 2:1.
[0026] The ratio of anhydrous ethanol, ethyl cellulose and modified sulfonated nanocellulose in step (4) is 100 mL: 4-10 g: 2-6 g; preferably 100 mL: 7 g: 3 g.
[0027] The mass ratio of the lignin nanoparticles, octadecylamine and ferulic acid in step (6) is 2-3:1-2:1-2; preferably 5:3:2.
[0028] The ratio of anhydrous ethanol, polyvinyl butyral and modified lignin nanoparticles in step (7) is 100 mL: 5-20 g: 1-2 g; preferably 100 mL: 10 g: 1 g.
[0029] The mass ratio of the oil-resistant solution to the water-resistant solution in step (8) is 1-3:1-3; preferably 1:1.
[0030] The coating in step (9) is performed using a roll coater.
[0031] The coating conditions in step (9) are as follows: a coating rate of 4 to 6 cm / s and a coating amount of 6 to 10 g / m 2 .
[0032] The drying conditions in step (9) are drying at 40 to 60° C. for 20 to 40 minutes.
[0033] The filtration was performed using filter paper with a pore size of 0.3 μm.
[0034] Unless otherwise specified, the solutions described are all solutions prepared with water as solvent.
[0035] A biomass-based water-resistant and oil-resistant packaging paper is prepared according to the above preparation method.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] (1) Provided is a method for preparing a biomass-based water-resistant and oil-resistant packaging paper, wherein the base paper is pretreated with a calcium chloride solution, and a homemade modified sulfonated Sargassum fusiformis nanocellulose solution and an ethyl cellulose solution are compounded to prepare an oil-resistant coating, and an oleophobic group (SO4 2- ,-COO - ), combined with ethyl cellulose to form an oleophobic film on the surface of paper, so as to achieve the purpose of filling the pores on the surface of paper and significantly improve the oil resistance of paper; and Ca 2+ -COO in Sargassum fusiformis nanocellulose - A cross-linking effect occurs, which makes the oil-resistant coating tightly bonded to the paper, thus improving the mechanical properties of the paper.
[0038] (2) The homemade modified lignin nanoparticle solution and polyvinyl butyral solution are compounded to prepare a water-resistant coating, which is coated on the surface of the base paper to give the paper excellent water-resistant effect, and the mechanical properties of the paper are further improved.
[0039] (3) The biomass-based water-resistant and oil-resistant packaging paper provided by the present invention uses Sargassum fusiformis, cellulose derivatives, lignin, etc. as main raw materials, all of which are natural biomass-based polymers. The prepared water-resistant and oil-resistant paper is fluorine-free, green and environmentally friendly, completely biodegradable, harmless to the environment and human body, and the preparation method is simple and can be used to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1This is the oil resistance test result in Example 5.
[0041] Figure 2 This is the water resistance test result in Example 5.
[0042] Figure 3 This is the tensile strength test result in Example 5.
[0043] Figure 4 This is the air permeability test result in Example 5.
[0044] Figure 5 This is the water vapor transmission rate test result in Example 5.
[0045] Figure 6 This is the degradation performance test result in Example 5.
[0046] Figure 7 These are photographs of paper prepared in Example 1 and untreated paper; the left picture is untreated paper, and the right picture is paper prepared in Example 1. DETAILED DESCRIPTION
[0047] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0048] If no specific experimental conditions are specified in the following embodiments, conventional experimental conditions or experimental conditions recommended by the reagent company are generally followed. The materials and reagents used, unless otherwise specified, are all reagents and materials obtained from commercial sources.
[0049] Source of raw materials:
[0050] Base paper: purchased from Guangxi Hezhou Red Star Paper Co., Ltd., the product name is white kraft paper, the product weight is 40g / m 2 ;
[0051] Sargassum: purchased from Rongcheng Three Penguins E-commerce Co., Ltd.
[0052] Ethyl cellulose: purchased from Guangzhou Huayu Biotechnology Co., Ltd.;
[0053] Alkali lignin: purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.;
[0054] Polyvinyl butyral: purchased from Guangdong Fangxin Biotechnology Co., Ltd.
[0055] Example 1
[0056] A method for preparing biomass-based water-resistant and oil-resistant packaging paper comprises the following steps:
[0057] (1) Calcium chloride is added to deionized water and mixed evenly to obtain a calcium chloride solution with a mass concentration of 2.0%; base paper is immersed in 100 mL of the calcium chloride solution for 6 minutes, and then the paper is placed in a vacuum drying oven and dried at 40° C. for 10 minutes to obtain base paper pretreated with calcium chloride.
[0058] (2) 400g of Sargassum fusiformis (absolute dry mass) was soaked in 2L of deionized water for 24h, and a Na2CO3 solution with a mass concentration of 20% was prepared at the same time. The soaked Sargassum fusiformis was placed in the 2L Na2CO3 solution and mixed evenly for 1h, and then placed in a 60°C oven for drying for 24h; the dried Sargassum fusiformis was fully washed with deionized water, placed in 500mL of acetic acid solution with a mass percentage concentration of 3%, and fully reacted for 2h, and then 50mL of H2O2 solution with a mass concentration of 30% was added, and after reacting for 2h, it was fully washed with deionized water for 20 times. Finally, 500mL of deionized water was added to the Sargassum fusiformis product, and then homogenized at 200MPa for 20 times, and finally filtered at a pressure of -0.09MPa to obtain pure Sargassum fusiformis nanocellulose.
[0059] (3) Take 100 mL of anhydrous ethanol and heat it at 60°C (closed container), add 10 g of sodium dodecyl sulfate thereto, and stir for 40 minutes to obtain a sodium dodecyl sulfate solution; add 5 g of Sargassum fusiformis nanocellulose to the sodium dodecyl sulfate solution, continue heating and stirring for 60 minutes to carry out the modification reaction, and after the reaction is completed, filter under a pressure of -0.09 MPa (filter paper pore size 0.3 μm) to obtain modified nanocellulose. Finally, the modified nanocellulose is washed with deionized water 10 times and ultrasonically treated at 200 W power for 30 minutes to obtain pure modified sulfonated nanocellulose.
[0060] (4) Take 100 mL of anhydrous ethanol and heat it at 40° C., add 7 g of ethyl cellulose thereto, stir for 30 min to obtain an ethyl cellulose solution, then add 3 g of the modified sulfonated nanocellulose prepared in step (3) thereto, continue heating and stirring for 30 min, and obtain an oil-resistant solution.
[0061] (5) Take 300 mL of anhydrous ethanol and heat it at 50°C, add 20 g of alkali lignin thereto, stir for 60 min, and after sufficient reaction, add 100 mL of deionized water and continue stirring for 30 min. Collect the supernatant and treat it in a high-speed centrifuge at 5000 rpm for 20 min, then use a rotary evaporator at 200 rpm for 30 min to remove ethanol to obtain lignin nanoparticles; take 5 g of lignin nanoparticles, 3 g of octadecylamine and 2 g of ferulic acid in 300 mL of ethanol solution, heat and stir at 60°C for 4 h, wait for the sample to cool after sufficient reaction, filter it with a filter with a pore size of 0.3 μm, and dry it for 12 h to obtain modified lignin nanoparticles.
[0062] (6) 300 mL of anhydrous ethanol was heated at 50° C. 30 g of polyvinyl butyral was added thereto, and the mixture was stirred for 40 min to obtain a polyvinyl butyral solution. 3 g of modified lignin nanoparticles was then added thereto, and the mixture was heated and stirred for 30 min to obtain an aqueous solution.
[0063] (7) 50 g of the oil-resistant solution and 50 g of the water-resistant solution were mixed, stirred on a magnetic stirrer for 30 min, and then ultrasonically treated at 200 W for 20 min to obtain a uniformly mixed water-resistant and oil-resistant composite solution. The composite solution was then uniformly coated on the surface of the base paper prepared in step (1) on a roller coater at a coating rate of 5 cm / s and a coating amount of 8 g / m 2 Finally, the paper is placed in a vacuum drying oven at a drying temperature of 50° C. for 30 minutes to obtain the biomass-based water-resistant and oil-resistant packaging paper.
[0064] Example 2
[0065] A method for preparing biomass-based water-resistant and oil-resistant packaging paper comprises the following steps:
[0066] (1) Calcium chloride is added to deionized water and mixed evenly to obtain a calcium chloride solution with a mass concentration of 1.0%; base paper is immersed in 100 mL of the calcium chloride solution for 8 minutes, and then the paper is placed in a vacuum drying oven and dried at 50° C. for 5 minutes to obtain base paper pretreated with calcium chloride.
[0067] (2) 300g of Sargassum fusiformis was soaked in 2L of deionized water for 36 hours, and a Na2CO3 solution with a mass concentration of 20% was prepared at the same time. The soaked Sargassum fusiformis was placed in the 2L Na2CO3 solution and mixed evenly for 1 hour, and then placed in a 70°C oven for drying for 24 hours; the dried Sargassum fusiformis was fully washed with deionized water, placed in 500mL of acetic acid solution with a mass percentage concentration of 3%, and fully reacted for 2 hours, and then 50mL of H2O2 solution with a mass concentration of 30% was added. After reacting for 2 hours, it was fully washed with deionized water for 15 times. Finally, deionized water was added to the Sargassum fusiformis product, and then homogenized at 200MPa for 20 times to obtain pure Sargassum fusiformis nanocellulose.
[0068] (3) 100 mL of anhydrous ethanol was heated at 60° C., 5 g of sodium dodecyl sulfate was added thereto, and the mixture was stirred for 40 min to obtain a sodium dodecyl sulfate solution; 5 g of Sargassum fusiformis nanocellulose was added to the sodium dodecyl sulfate solution, and the mixture was heated and stirred for 60 min to carry out the modification reaction. After the reaction was completed, the mixture was filtered at a pressure of -0.09 MPa (pore size of filter paper: 0.3 μm) to obtain modified nanocellulose. The modified nanocellulose was then washed 20 times with deionized water and ultrasonically treated at a power of 200 W for 40 min to obtain pure modified sulfonated nanocellulose.
[0069] (4) Take 100 mL of anhydrous ethanol and heat it at 40° C., add 8 g of ethyl cellulose thereto, stir for 30 min to obtain an ethyl cellulose solution, then add 2 g of the modified sulfonated nanocellulose prepared in step (3) thereto, continue heating and stirring for 30 min, and obtain an oil-resistant solution.
[0070] (5) Take 300 mL of anhydrous ethanol and heat it at 50°C, add 15 g of alkali lignin thereto, stir for 60 min, and after sufficient reaction, add 100 mL of deionized water and continue stirring for 30 min. Collect the supernatant and treat it in a high-speed centrifuge at 5000 rpm for 20 min, then use a rotary evaporator at 200 rpm for 30 min to remove ethanol to obtain lignin nanoparticles; take 5 g of lignin nanoparticles, 4 g of octadecylamine and 2 g of ferulic acid in 300 mL of ethanol solution, heat and stir at 60°C for 4 h, wait for the sample to cool after sufficient reaction, filter it with a filter with a pore size of 0.3 μ, and dry it for 24 h to obtain modified lignin nanoparticles.
[0071] (6) 300 mL of ethanol was heated at 50° C. 35 g of polyvinyl butyral was added thereto, and the mixture was stirred for 40 min to obtain a polyvinyl butyral solution. 4 g of modified lignin nanoparticles was then added thereto, and the mixture was heated and stirred for 30 min to obtain an aqueous solution.
[0072] (7) 60 g of the oil-resistant solution and 40 g of the water-resistant solution were mixed, stirred on a magnetic stirrer for 30 min, and then ultrasonically treated at 200 W for 20 min to obtain a uniformly mixed water-resistant and oil-resistant composite solution. The composite solution was then uniformly coated on the surface of the base paper prepared in step (1) on a roller coater at a coating rate of 6 cm / s and a coating amount of 9 g / m 2 Finally, the paper is placed in a vacuum drying oven at a drying temperature of 50° C. for 30 minutes to obtain the biomass-based water-resistant and oil-resistant packaging paper.
[0073] Example 3
[0074] A method for preparing biomass-based water-resistant and oil-resistant packaging paper comprises the following steps:
[0075] (1) Calcium chloride is added to deionized water and mixed evenly to obtain a calcium chloride solution with a mass concentration of 3.0%; base paper is immersed in 100 mL of the calcium chloride solution for 6 minutes, and then the paper is placed in a vacuum drying oven and dried at 30° C. for 10 minutes to obtain base paper pretreated with calcium chloride.
[0076] (2) Soak 200g of Sargassum fusiformis in 2L of deionized water for 24h, prepare a 20% Na2CO3 solution, put the soaked Sargassum fusiformis in the 2L Na2CO3 solution and mix evenly for 1h, then put it in a 60°C oven to dry for 24h; the dried Sargassum fusiformis is fully washed with deionized water, put into 500mL of acetic acid solution with a mass percentage concentration of 3%, fully react for 2h, add 50mL of H2O2 solution with a mass concentration of 30%, react for 2h, and then wash it with deionized water for 20 times. Finally, deionized water is added to the Sargassum fusiformis product, and then homogenized at 200MPa for 20 times to obtain pure Sargassum fusiformis nanocellulose.
[0077] (3) 100 mL of anhydrous ethanol was heated at 60° C., 20 g of sodium dodecyl sulfate was added thereto, and the mixture was stirred for 40 min to obtain a sodium dodecyl sulfate solution; 10 g of Sargassum fusiformis nanocellulose was added to the sodium dodecyl sulfate solution, and the mixture was heated and stirred for 60 min to carry out the modification reaction. After the reaction was completed, the mixture was filtered at a pressure of -0.09 MPa (pore size of filter paper: 0.3 μm) to obtain modified nanocellulose. The modified nanocellulose was then washed 20 times with deionized water and ultrasonically treated at a power of 200 W for 40 min to obtain pure modified sulfonated nanocellulose.
[0078] (4) Take 100 mL of ethanol and heat it at 40° C., add 10 g of ethyl cellulose thereto, stir for 30 min to obtain an ethyl cellulose solution, then add 5 g of the modified sulfonated nanocellulose prepared in step (3) thereto, continue heating and stirring for 30 min, and obtain an oil-resistant solution.
[0079] (5) Take 300 mL of anhydrous ethanol and heat it at 50°C, add 20 g of alkali lignin thereto, stir for 60 minutes, and after sufficient reaction, add 100 mL of deionized water and continue stirring for 30 minutes. Collect the supernatant and treat it in a high-speed centrifuge at 5000 rpm for 20 minutes, then use a rotary evaporator at 200 rpm for 30 minutes to remove ethanol to obtain lignin nanoparticles; take 5 g of lignin nanoparticles, 3 g of octadecylamine and 2 g of ferulic acid in 300 mL of ethanol solution, heat and stir at 60°C for 4 hours, wait for the sample to cool after sufficient reaction, filter it with a filter with a pore size of 0.3μ, and dry it for 12 hours to obtain modified lignin nanoparticles.
[0080] (6) 300 mL of anhydrous ethanol was heated at 50° C. 30 g of polyvinyl butyral was added thereto, and the mixture was stirred for 40 min to obtain a polyvinyl butyral solution. 6 g of modified lignin nanoparticles was then added thereto, and the mixture was heated and stirred for 30 min to obtain an aqueous solution.
[0081] (7) 40 g of the oil-resistant solution and 60 g of the water-resistant solution were mixed, stirred on a magnetic stirrer for 30 min, and then ultrasonically treated at 200 W for 20 min to obtain a uniformly mixed water-resistant and oil-resistant composite solution. The composite solution was then uniformly coated on the surface of the base paper prepared in step (1) on a roller coater at a coating rate of 6 cm / s and a coating amount of 10 g / m 2 Finally, the paper is placed in a vacuum drying oven at a drying temperature of 50° C. for 30 minutes to obtain the biomass-based water-resistant and oil-resistant packaging paper.
[0082] Example 4
[0083] A method for preparing biomass-based water-resistant and oil-resistant packaging paper comprises the following steps:
[0084] (1) Calcium chloride is added to deionized water and mixed evenly to obtain a calcium chloride solution with a mass concentration of 2.0%; base paper is immersed in 100 mL of the calcium chloride solution for 5 minutes, and then the paper is placed in a vacuum drying oven and dried at 40° C. for 10 minutes to obtain base paper pretreated with calcium chloride.
[0085] (2) 400g of Sargassum fusiformis was soaked in 2L of deionized water for 24h, and a Na2CO3 solution with a mass concentration of 20% was prepared at the same time. The soaked Sargassum fusiformis was placed in the 2L Na2CO3 solution and mixed evenly for 1h, and then placed in a 60°C oven for drying for 24h; the dried Sargassum fusiformis was fully washed with deionized water, placed in 500mL of acetic acid solution with a mass percentage concentration of 3%, and fully reacted for 2h, and then 50mL of H2O2 solution with a mass concentration of 30% was added, and after reacting for 2h, it was fully washed with deionized water for 20 times. Finally, deionized water was added to the Sargassum fusiformis product, and then homogenized at 200MPa for 20 times to obtain pure Sargassum fusiformis nanocellulose.
[0086] (3) 100 mL of anhydrous ethanol was heated at 60° C., 10 g of sodium dodecyl sulfate was added thereto, and the mixture was stirred for 40 min to obtain a sodium dodecyl sulfate solution; 5 g of Sargassum fusiformis nanocellulose was added to the sodium dodecyl sulfate solution, and the mixture was heated and stirred for 60 min to carry out the modification reaction. After the reaction was completed, the mixture was filtered at a pressure of -0.09 MPa (pore size of filter paper: 0.3 μm) to obtain modified nanocellulose. The modified nanocellulose was then washed with deionized water for 10 times and ultrasonically treated at a power of 200 W for 30 min to obtain pure modified sulfonated nanocellulose.
[0087] (4) Take 100 mL of anhydrous ethanol and heat it at 40° C., add 7 g of ethyl cellulose thereto, stir for 30 min to obtain an ethyl cellulose solution, then add 3 g of the modified sulfonated nanocellulose prepared in step (3) thereto, continue heating and stirring for 30 min, and obtain an oil-resistant solution.
[0088] (5) Take 300 mL of anhydrous ethanol and heat it at 50°C, add 20 g of alkali lignin thereto, stir for 60 minutes, and after sufficient reaction, add 100 mL of deionized water and continue stirring for 30 minutes. Collect the supernatant and treat it in a high-speed centrifuge at 5000 rpm for 20 minutes, then use a rotary evaporator at 200 rpm for 30 minutes to remove ethanol to obtain lignin nanoparticles; take 5 g of lignin nanoparticles, 3 g of octadecylamine and 2 g of ferulic acid in 300 mL of ethanol solution, heat and stir at 60°C for 4 hours, wait for the sample to cool after sufficient reaction, filter it with a filter with a pore size of 0.3μ, and dry it for 12 hours to obtain modified lignin nanoparticles.
[0089] (6) 300 mL of anhydrous ethanol was heated at 50° C. 30 g of polyvinyl butyral was added thereto, and the mixture was stirred for 40 min to obtain a polyvinyl butyral solution. 3 g of modified lignin nanoparticles was then added thereto, and the mixture was heated and stirred for 30 min to obtain an aqueous solution.
[0090] (7) 30 g of the oil-resistant solution and 70 g of the water-resistant solution were mixed, stirred on a magnetic stirrer for 30 min, and then ultrasonically treated at 200 W for 20 min to obtain a uniformly mixed water-resistant and oil-resistant composite solution. The composite solution was then uniformly coated on the surface of the base paper prepared in step (1) on a roller coater at a coating rate of 5 cm / s and a coating amount of 8 g / m 2 Finally, the paper is placed in a vacuum drying oven at a drying temperature of 50° C. for 30 minutes to obtain the biomass-based water-resistant and oil-resistant packaging paper.
[0091] Comparative Example 1
[0092] Referring to the preparation method of Example 1, the operation of pre-treating the base paper with the calcium chloride solution in Example 1 is omitted, that is, the water-resistant and oil-resistant solution is directly coated on the surface of the base paper, and other operations are consistent with Example 1 to obtain biomass-based water-resistant and oil-resistant packaging paper.
[0093] Comparative Example 2
[0094] Referring to the preparation method of Example 1, the process of preparing the modified sulfonated nanocellulose solution in Example 1 is omitted, that is, the oil-resistant layer is only composed of the ethyl cellulose solution, and other operations are consistent with Example 1 to prepare biomass-based water-resistant and oil-resistant packaging paper.
[0095] Comparative Example 3
[0096] Referring to the preparation method of Example 1, the process of preparing the ethyl cellulose solution in Example 1 is omitted, that is, the oil-resistant layer is only composed of the modified sulfonated nanocellulose solution, and other operations are consistent with Example 1 to prepare biomass-based water-resistant and oil-resistant packaging paper.
[0097] Comparative Example 4
[0098] Referring to the preparation method of Example 1, the process of preparing the modified lignin nanoparticle solution in Example 1 is omitted, that is, the water-resistant layer is only composed of the polyvinyl butyral solution, and other operations are consistent with Example 1 to prepare biomass-based water-resistant and oil-resistant packaging paper.
[0099] Comparative Example 5
[0100] Referring to the preparation method of Example 1, the process of preparing the polyvinyl butyral solution in Example 1 is omitted, that is, the water-resistant layer is only composed of the modified lignin nanoparticle solution, and other operations are consistent with Example 1 to prepare biomass-based water-resistant and oil-resistant packaging paper.
[0101] Comparative Example 6
[0102] Referring to the preparation method of Example 1, the difference is that coniferous wood pulp is used to replace Sargassum fusiformis nanocellulose, and specifically, step (2) is modified as follows:
[0103] (2) 20 g of bleached coniferous pulp was added to a TEMPO / NaClO / NaBr system (0.05 g TEMPO, 0.5 g NaBr and 50 mL NaClO dissolved in 500 mL deionized water), the pH value of the reaction system was adjusted to 10 with 0.1 mol / L HCl and NaOH, and then homogenized 15 times at 180 MPa. Coniferous pulp nanocellulose was obtained after filtration.
[0104] The fiber length and properties of the prepared coniferous wood pulp nanocellulose are similar to those of the Sargassum fusiformis nanocellulose prepared in step (2), and modified cellulose can also be prepared. Other operations are consistent with Example 1 to prepare biomass-based water-resistant and oil-resistant packaging paper.
[0105] Comparative Example 7
[0106] Referring to the preparation method of Example 1, the ethyl cellulose in Example 1 was replaced by an equal mass of methyl cellulose, that is, the oil-resistant layer was composed of Sargassum-modified sulfonated nanocellulose and methyl cellulose solution, and other operations were consistent with Example 1 to obtain biomass-based water-resistant and oil-resistant packaging paper.
[0107] Comparative Example 8
[0108] Referring to the preparation method of Example 1, the polyvinyl butyral in Example 1 is replaced by an equal mass of carnauba wax, that is, the water-resistant layer is composed of modified lignin nanoparticles and carnauba wax solution, and other operations are consistent with Example 1 to obtain biomass-based water-resistant and oil-resistant packaging paper.
[0109] Comparative Example 9
[0110] Referring to the preparation method of Example 1, the modified lignin nanoparticles prepared in Example 1 were replaced by modified lignin of equal mass, that is, the water-resistant layer was composed of modified lignin and polyvinyl butyral solution, and other operations were consistent with Example 1 to obtain biomass-based water-resistant and oil-resistant packaging paper.
[0111] Example 5 Product Performance Test
[0112] The water-resistant and oil-resistant packaging papers prepared in the examples and comparative examples were subjected to performance tests, and the test methods were as follows:
[0113] (1) Oil resistance test:
[0114] Refer to the standard TAPPI T 559-"Grease resistance test for paper and paperboard" method.
[0115] (2) Water resistance test:
[0116] GB / T1540-2002 "Determination of water absorption of paper and paperboard-Cobber method".
[0117] (3) Tensile strength test:
[0118] GB / T12914-2018 "Determination of tensile strength of paper and paperboard - Constant rate of tension method".
[0119] (4) Air permeability test:
[0120] GB / T458-2008 "Determination of air permeability of paper and paperboard".
[0121] (5) Water vapor transmission rate test:
[0122] GB / T22921-2008 "Determination of water vapor transmission rate of paper and paperboard thin sheets - Dynamic airflow method and static gas method".
[0123] (6) Degradation performance test:
[0124] GB / T39951-2021 "Evaluation method for degradation performance of disposable paper products".
[0125] The test results are as follows:
[0126] The experimental results are as follows Figures 1 to 7 As shown, it can be seen that:
[0127] The difference between Comparative Example 1 and Example 1 is that the base paper is not pretreated with calcium chloride solution; 2+ It exists and cannot react with -COOH in modified sulfonated nanocellulose. - Combined with the above, the tensile strength of water-resistant and oil-resistant paper shows a downward trend.
[0128] The difference between Comparative Example 2 and Example 1 is that the oil-resistant layer is only composed of ethyl cellulose solution; since the oil-resistant layer is not modified by the sulfonated nanocellulose solution, the holes on the surface of the base paper are not fully filled, resulting in a downward trend in the oil-proof performance and tensile strength of the water-resistant and oil-resistant paper, and an upward trend in the water vapor permeability and air permeability, thereby reducing the overall performance of the water-resistant and oil-resistant paper.
[0129] The difference between Comparative Example 3 and Example 1 is that the oil-resistant layer is only composed of modified sulfonated nanocellulose solution; since the oil-resistant layer does not contain ethyl cellulose solution, the holes on the surface of the base paper are not fully filled, resulting in a downward trend in the oil-proof performance and tensile strength of the water-resistant and oil-resistant paper, and an upward trend in the water vapor permeability and air permeability, thereby reducing the overall performance of the water-resistant and oil-resistant paper.
[0130] The difference between Comparative Example 4 and Example 1 is that the water-resistant layer is only composed of polyvinyl butyral solution; since the water-resistant layer does not have a modified lignin nanoparticle solution, the pores on the surface of the base paper are not fully filled, resulting in a downward trend in the water resistance and tensile strength of the water-resistant and oil-resistant paper, and an upward trend in the water vapor permeability and air permeability, thereby reducing the overall performance of the water-resistant and oil-resistant paper.
[0131] The difference between Comparative Example 5 and Example 1 is that the water-resistant layer is only composed of a modified lignin nanoparticle solution; since the water-resistant layer does not contain a polyvinyl butyral solution, the holes on the surface of the base paper are not fully filled, resulting in a downward trend in the water resistance and tensile strength of the water-resistant and oil-resistant paper, and an upward trend in the water vapor permeability and air permeability, thereby reducing the overall performance of the water-resistant and oil-resistant paper.
[0132] The difference between Comparative Example 6 and Example 1 is that the oil-resistant layer is composed of coniferous wood modified sulfonated nanocellulose and ethyl cellulose solution; since the oil-resistant layer does not have the sulfonated nanocellulose solution modified by Sargassum fusiformis, the oil-proof performance and tensile strength of the water-resistant and oil-resistant paper show a downward trend, and the water vapor permeability and air permeability show an upward trend, and the overall performance of the water-resistant and oil-resistant paper is reduced.
[0133] The difference between Comparative Example 7 and Example 1 is that the oil-resistant layer is composed of sulfonated nanocellulose modified by Sargassum fusiformis and methylcellulose solution; since equal mass of methylcellulose increases the viscosity of the solution, there are some difficulties in coating, and the film-forming property of methylcellulose is poor, resulting in a downward trend in the oil-proof performance, water-proof performance, and tensile strength of the water-resistant and oil-resistant paper, an upward trend in water vapor permeability and air permeability, and a reduction in the overall performance of the water-resistant and oil-resistant paper.
[0134] The difference between Comparative Example 8 and Example 1 is that the water-resistant layer is composed of modified lignin nanoparticles and Brazilian palm wax solution; since the water-resistant layer does not contain polyvinyl butyral solution, the film-forming property of the base paper surface deteriorates and the pores are not fully filled, resulting in a downward trend in the water resistance and tensile strength of the water-resistant and oil-resistant paper, an upward trend in the water vapor permeability and air permeability, and a reduction in the overall performance of the water-resistant and oil-resistant paper.
[0135] The difference between Comparative Example 9 and Example 1 is that the water-resistant layer is composed of modified lignin and polyvinyl butyral solution; since the water-resistant layer does not have a modified lignin nanoparticle solution, the tiny holes on the surface of the base paper are not fully filled, resulting in a downward trend in the water resistance and tensile strength of the water-resistant and oil-resistant paper, an upward trend in the water vapor permeability and air permeability, and a reduction in the overall performance of the water-resistant and oil-resistant paper.
[0136] To sum up, the biomass-based water-resistant and oil-resistant packaging paper prepared in the embodiment of the present invention adopts a composite water-resistant / oil-resistant layer, the coating is more tightly combined with the paper, and has a high oil resistance grade, high tensile strength, low water vapor permeability, low air permeability, good water resistance and degradation performance.
[0137] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing biomass-based water-resistant and oil-resistant packaging paper, characterized in that The following steps are involved: (1) impregnating base paper with a calcium chloride solution having a concentration of 1 to 3% for 4 to 10 minutes, and obtaining pretreated base paper after drying; (2) Using biomass raw materials to prepare nanocellulose; (3) adding sodium dodecyl sulfate to anhydrous ethanol, stirring and heating at 50-70° C. for reaction for 30-50 min, then adding the nanocellulose obtained in step (2), continuing to stir and heat for reaction, washing, and ultrasonicating to obtain modified sulfonated nanocellulose; (4) adding ethyl cellulose to anhydrous ethanol, stirring and heating at 30-50° C. for 20-40 min, then adding the modified sulfonated nanocellulose obtained in step (3) and continuing to stir and heat for 20-40 min to obtain an oil-resistant solution; (5) adding alkali lignin to anhydrous ethanol, stirring and heating at 40-60° C. for 40-80 min, then adding water and continuing stirring and heating for 20-40 min, collecting the supernatant, centrifuging at 4000-6000 rpm for 10-30 min, and removing ethanol by rotary evaporation to obtain lignin nanoparticles; (6) adding the lignin nanoparticles prepared in step (5), octadecylamine and ferulic acid to anhydrous ethanol, stirring and heating at 50-70° C. for 3-5 h, cooling, filtering and drying to obtain modified lignin nanoparticles; (7) adding polyvinyl butyral to anhydrous ethanol, stirring and heating at 40-60° C. for 30-50 min, then adding the modified lignin nanoparticles obtained in step (6), and continuing to stir and heat for 20-40 min to obtain an aqueous solution-resistant nanoparticle; (8) stirring and mixing the oil-resistant solution obtained in step (4) and the water-resistant aqueous solution obtained in step (7) for 20 to 40 minutes, and ultrasonicating to obtain a water-resistant and oil-resistant composite solution; (9) coating the water-resistant and oil-resistant composite solution obtained in step (8) on the pretreated base paper obtained in step (1), and drying the solution to obtain biomass-based water-resistant and oil-resistant packaging paper.
2. The preparation method according to claim 1, characterized in that: The base paper in step (1) is a paper made from raw wood pulp and having a rough surface; The drying condition in step (1) is drying at 30-50° C. for 5-20 min; The biomass raw material described in step (2) is a biomass raw material rich in cellulose.
3. The preparation method according to claim 2, characterized in that: When the biomass raw material is coniferous wood pulp, the preparation method of nanocellulose is: 20 g of bleached softwood pulp was added to a solution obtained by dissolving 0.05 g of TEMPO, 0.5 g of NaBr and 50 mL of NaClO in 500 mL of deionized water, and the pH value of the reaction system was adjusted to 10 with 0.1 mol / L HCl and NaOH, and then homogenized at 180 MPa for 15 times, and filtered to obtain softwood pulp nanocellulose; When the biomass raw material is Sargassum fusiformis, the preparation method of nanocellulose is: The dried Sargassum fusiformis is soaked in water, the soaked Sargassum fusiformis is placed in a 20wt% Na2CO3 solution and mixed evenly for 1 hour, then dried, washed, placed in a 3wt% acetic acid solution to react for 2 hours, then added with a 30wt% H2O2 solution to react for 2 hours, washed, added with deionized water, and then homogenized 20 times at 200MPa, and filtered to obtain Sargassum fusiformis nanocellulose.
4. The preparation method according to claim 1, characterized in that: The mass ratio of sodium dodecyl sulfate to nanocellulose in step (3) is 1-2:1-2; The ratio of anhydrous ethanol, ethyl cellulose and modified sulfonated nanocellulose in step (4) is 100 mL: 4-10 g: 2-6 g.
5. The preparation method according to claim 4, characterized in that: The mass ratio of sodium dodecyl sulfate to nanocellulose in step (3) is 2:1; The ratio of anhydrous ethanol, ethyl cellulose and modified sulfonated nanocellulose in step (4) is 100 mL: 7 g: 3 g.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the lignin nanoparticles, octadecylamine and ferulic acid in step (6) is 2-3:1-2:1-2; The ratio of anhydrous ethanol, polyvinyl butyral and modified lignin nanoparticles in step (7) is 100 mL: 5-20 g: 1-2 g.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the lignin nanoparticles, octadecylamine and ferulic acid in step (6) is 5:3:2; The ratio of anhydrous ethanol, polyvinyl butyral and modified lignin nanoparticles in step (7) is 100 mL: 10 g: 1 g.
8. The preparation method according to claim 1, characterized in that: The mass ratio of the oil-resistant solution to the water-resistant solution in step (8) is 1-3:1-3.
9. The preparation method according to claim 1, characterized in that: The coating in step (9) is performed using a roller coater; The coating conditions in step (9) are as follows: a coating rate of 4 to 6 cm / s and a coating amount of 6 to 10 g / m 2 ; The drying conditions in step (9) are drying at 40 to 60° C. for 20 to 40 minutes.
10. A biomass-based water-resistant and oil-resistant packaging paper, prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of fluoride-free degradable waterproof and oilproof packaging paper
CN116084209A
Preparation method of waterproof and oilproof barrier material and application of waterproof and oilproof barrier material in waterproof and oilproof paper
CN117265909A
Lignin micro-nano particles prepared by using high-pressure homogenization method and application of lignin micro-nano particles
CN118546399A
Water, grease and heat resistant bio-based products and method of making same
US20160145480A1
